Гора троллей: [сказочная повесть] / Кэтрин Лэнгриш - Лэнгриш Кэтрин (Серия "Внеклассное чтение", 2007)
Экземпляры: М/а ДБ (20160506) / Инвентарный номер: 104301 / Цена: 150.70 / Авт.знак: Л 92 / ГРНТИ: 17.82 / ББК: 84(7Сое)